2019
DOI: 10.1371/journal.pone.0210153
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of body weight is an important determinant for the risk of ischemic stroke: A nationwide population-based cohort study

Abstract: BackgroundOverweight is known as a risk factor for ischemic stroke. However, the effect of weight change on the development of ischemic stroke remains controversial. We investigated the relationship between weight change and the risk of ischemic stroke using a nationwide population-based cohort.MethodsOur study enrolled 11,084,683 participants (Mean age 49.7±13.5 years, range 20–114 years) in the Korean National Health Screening Program from 2009 to 2012. Weight change was calculated using the difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Fluctuations, as measured by standard deviation, in BMI were positively correlated with stroke risk. These findings are consistent with several previous studies showing that the risk of stroke increases in individuals who lose or gain weight ( 41 ). The associations between BMI and stroke risk were inconclusive, possibly reflecting a previously observed weight paradox in stroke outcomes, particularly in the elderly (>75% of our study participants were over 60 years) ( 42 , 43 ).…”
Section: Discussionsupporting
confidence: 93%
“…Fluctuations, as measured by standard deviation, in BMI were positively correlated with stroke risk. These findings are consistent with several previous studies showing that the risk of stroke increases in individuals who lose or gain weight ( 41 ). The associations between BMI and stroke risk were inconclusive, possibly reflecting a previously observed weight paradox in stroke outcomes, particularly in the elderly (>75% of our study participants were over 60 years) ( 42 , 43 ).…”
Section: Discussionsupporting
confidence: 93%
“… 97 Alternatively, a cohort study also suggests that not only weight gain but also weight loss more than 5% should be emphasized to the increased incidence rate of Transient ischemic attack (TIA). 98 Therefore, weight management to be optimal to prevent a stroke rate.…”
Section: Discussionmentioning
confidence: 99%
“…The current study has also found that obese and overweight individuals are at greater risk of developing stroke. The study conducted by Cho et al suggested that weight gain is associated with an increased incidence rate of TIA [ 24 ]. Thus, management of weight needs to be an optimal method for preventing stroke.…”
Section: Discussionmentioning
confidence: 99%